Implementation of Yasin and Tahlil Traditions in Building Social Solidarity in Gandarum Village, Kajen District, Pekalongan Regency - Siti Chumaerotur Rofiatur Risqoh; Nur Khotimah (Interdisciplinary Social Studies, 2025)
The Yasin and Tahlil traditions are religious activities that have taken root in the lives of Islamic communities in Indonesia, including in Gandarum Village, Kajen District, Pekalongan Regency. This study aims to analyze how the implementation of the Yasin and Tahlil traditions plays a role in building social solidarity of the local community. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the Yasin and Tahlil traditions not only function as a means of worship, but also as a medium to strengthen social relationships, strengthen empathy, mutual cooperation, and strengthen local religious and cultural identity. This tradition is an effective forum in maintaining social harmony and strengthening the value of togetherness in the midst of modernization trends that tend to be individualistic.